Assessment of the upper respiratory tract in patients eligible for treatment with transverse maxillary expansion - Dargiewicz, Ewelina; Szarmach, Izabela J.; Sawczuk, Magdalena (Forum Ortodontyczne / Orthodontic Forum, 2018)
Transverse maxillary hypoplasia may negatively affect respiration. Maxillary narrowing has to be treated early. An appliance for Rapid Maxillary Expansion (RME) is the most common method, and it aims to expand the skeletal base and maintain this width until a new bone has been formed to fill in the fissure. Aim. Comparison of the results of measurements of bone structures and of the upper airways on lateral teleroentgenograms of the head in patients with transverse maxillary hypoplasia and in patients with normal dimensions of the maxilla. Material and methods. The study was carried out in a group of 20 people with maxillary narrowing (10 girls and 10 boys) aged 7 to 10 years. The control group consisted of 20 lateral teleroentgenograms of patients (9 girls and 11 boys) of similar age treated for other malocclusions. The structures of the facial skeleton and the upper respiratory tract were assessed in teleroentgenograms after earlier determination of measurement points and planes according to selected parameters of the McNamara and Preston et al. methodology. The obtained results were analysed statistically using the Mann-Whitney's test. Results. Angular measurements showed statistically significantly smaller SNA and SNB angles in the study group compared to the control group. The analysis of linear measurements indicated a statistically significant larger dimension of the actual length of the midfacial segment Co-A) and distance between the Sella point and the posterior nasal spine (PNS-S), and a smaller dimension of the posterior facial height (PFH) in the study group compared to the control group. The highest differences in upper respiratory tract measurements were noted in the Ba-ho-PNS angle, which was lower in the study group. The result was not statistically significant. Conclusions. No significant differences in cephalometric measurements of the upper airways were observed. There is a need to extend studies to include groups of patients with features of night apnoea and maxillary narrowing. (Dargiewicz E, Szarmach IJ, Sawczuk M. Assessment of the upper respiratory tract in patients eligible for treatment with transverse maxillary expansion. Orthod Forum 2018; 14: 97-105)